Pengaruh Persepsi Konsumen terhadap Keputusan Pembelian pada Perum Bulog sub Divre Pematangsiantar - Mega Romauly Tampubolon; Muhammad Yunus; Liana Liana (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2019)
The purpose of this study is: to determine the effect of consumer perceptions on purchasing decisions at Perum Bulog Sub Divre Pematangsiantar. This study uses a library research design and field research. This type of data uses qualitative and quantitative data. Data sources are primary data and secondary data. Data collection was carried out by means of questionnaires, interviews, and documentation. Test the research instrument using the validity test and reliability test. The data analysis technique used is normality test, qualitative descriptive analysis, and quantitative descriptive analysis. The results of this study can be concluded as follows: Consumer perceptions have a positive and significant effect on purchasing decisions either simultaneously or partially. There is a strong and positive relationship between consumer perceptions of purchasing decisions. The level of purchase decisions can be explained by consumer perceptions. Consumer perceptions have a positive and significant effect on purchasing decisions at Perum Blog Sub Divre Pematangsiantar